Enhancing Torsional Behavior of Deep Beams Strengthened with NSM Steel and Basalt Bars under Repeated Pure Torsion - Salih, Noor M.; Waryosh, Waleed A. (Engineering, Technology & Applied Science Research, 2025)
This study investigates the torsional behavior of reinforced concrete deep beams enhanced through the Near-Surface Method (NSM), using steel and basalt bars under repeated torsional loads. Five beam specimens were cast and tested. One served as the unstrengthened reference, while the remaining four were reinforced using NSM bars on either two or four sides. The experimental program investigated the impact of reinforcing material (steel and basalt) and several strengthened faces. The results demonstrated that the NSM strengthening significantly enhanced the beams’ torsional resistance. When evaluated with the reference beam, the ultimate torque increased by 16.5% and 30.4% for the two-sided and four-sided steel structures, respectively, while the basalt bars exhibited enhancements of 33.0% and 46.0%, respectively. Furthermore, the longitudinal elongation at failure decreased by as much as 22.3% in the most effective configurations, indicating a significant enhancement in the deformation control. The study indicates that augmenting the number of reinforced faces and employing basalt bars achieves beneficial results in terms of strength and stiffness.